Digital Revolution in Public Communication Management: A Review of Opportunities and Challenges for Maluku Regional Police Public Relations in the Digital Era - Siregar, Kevin Chrisya; Sopacua, Yustina; Alfredo, Ronald (Universitas Pattimura, 2024)
This article examines the transformation of public communication management in the digital era, focusing on the case of the Maluku Regional Police (Polda Maluku). The study aims to explore both the opportunities and challenges brought about by digital developments in the field of public relations within law enforcement institutions. Using a qualitative approach, data were collected through in-depth interviews, observations, and document analysis to understand the dynamics of communication practices in the digital context. The findings reveal that digital platforms—such as social media, online news portals, and mobile applications—present valuable opportunities to enhance transparency, foster community engagement, and strengthen public trust. However, several challenges also emerge, including the spread of misinformation, data privacy concerns, and the urgency of timely crisis communication. Organizational factors such as digital readiness, infrastructure availability, leadership orientation, and internal culture further influence the effectiveness of digital communication strategies. The novelty of this study lies in its contextual focus on Polda Maluku, offering a nuanced analysis that connects digital transformation with institutional capability and socio-cultural environments. This article contributes to the development of social and humanities scholarship by providing a critical lens to understand how public institutions navigate the complexities of digital communication. It recommends the advancement of infrastructure, digital literacy, and regulatory frameworks as key steps toward responsive and inclusive public communication in the digital era.